2017
DOI: 10.1002/mnfr.201600992
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of a diet rich inBrassicavegetables is associated with a reduced abundance of sulphate-reducing bacteria: A randomised crossover study

Abstract: ScopeWe examined whether a Brassica‐rich diet was associated with an increase in the relative abundance of intestinal lactobacilli and sulphate‐reducing bacteria (SRB), or alteration to the composition of the gut microbiota, in healthy adults.Methods and resultsA randomised crossover study was performed with ten healthy adults who were fed a high‐ and a low‐Brassica diet for 2‐wk periods, with a 2‐wk washout phase separating the diets. The high‐Brassica diet consisted of six 84 g portions of broccoli, six 84 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 41 publications
(48 reference statements)
3
51
4
Order By: Relevance
“…Despite the individualized responses, four taxa were associated with the cruciferous vegetable diet: Eubacterium hallii , Phascolarctobacterium faecium , Alistipes putredinis , and Eggerthella spp. In another study also feeding cruciferous vegetables, the authors reported significant reductions in sulfate-reducing bacteria [ 65 ]. This is desirable, since sulfate is reduced to hydrogen sulfide by sulfate-reducing bacteria, which has been associated with several GI disorders [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the individualized responses, four taxa were associated with the cruciferous vegetable diet: Eubacterium hallii , Phascolarctobacterium faecium , Alistipes putredinis , and Eggerthella spp. In another study also feeding cruciferous vegetables, the authors reported significant reductions in sulfate-reducing bacteria [ 65 ]. This is desirable, since sulfate is reduced to hydrogen sulfide by sulfate-reducing bacteria, which has been associated with several GI disorders [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Burton et al, also found that there was an absence of the probiotic bacterial strains related to the two-week consumption of probiotic yoghurt after a three week wash-out period (n = 14) [39]. In a study by Kellingray et al, increased consumption of Brassica was associated with reduced relative abundance of sulphate-producing bacteria and members of Rikenellaceae, Ruminococcaceae, Mogibacteriaceae, and Clostridiales [40]. Though, they observed little evidence of carry-over effects of high-Brassica diet after a two-week wash-out periods.…”
Section: Effect Of Short-term Dietary Interventions On the Gut Microbmentioning
confidence: 96%
“…To minimize confounding factors (especially various disease status), we used search terms "diet" AND "gut microbiome" AND "healthy adult" and included only clinical studies in healthy participants that have detailed diet and gut microbiome information (Supplemental Figure 2). We identi ed 16 eligible clinical studies [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53] that included in total 771 subjects. Among them, 428 were females and 343 were males.…”
Section: Diet Could Potentially Affect the E Cacy Of Cancer Immunothementioning
confidence: 99%